Maladie hyperostosique et maladie goutteuse, une diathèse familiale en Normandie : Thaon, Calvados - Joël Blondiaux; Armelle Alduc-Le Bagousse; Xavier Demondion; Françoise Delahaye; Cécile Niel (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The architectural analysis and the complete archaeological survey of the old Saint Pierre parish church in Thaon (Calvados, France), dated to between the 7th and the 18th centuries, are in progress. Within the 12th century choir, fifteen burials have been excavated; all of them revealed mature skeletons. Four of these skeletons present features of hyperostosic disease. Besides hyperostosic disease, three of them display the features of erosive polyarthropathies mainly in the distal extremities. Two of these skeletons present ankylosis of the feet. Erosive lesions and ankyloses are compatible with gout. In the archaeological context of people buried side by side in a church chancel, this palaeopathological observation offers an almost caricatural look at possible genetic links with common overeating within an historical privileged group.